Cost-effectiveness of physical activity-oriented interventions for improving mental health: a systematic review - Noara Alhusseini; Tracy Kuo Lin; Kalin Werner; George Lin; Yasmin Altwaijri; Baian A. Baattaiah; Tim Bruckner; Reem AlAhmed; Abdulrahman Alkabbani; Reem F. Alsukait; Volkan Cetinkaya; Hazzaa M. Al-Hazzaa; et al. (BMC Public Health)
Abstract Question Are physical activity-oriented interventions for improving mental health conditions cost-effective? This study systematically identified and summarized published evidence on the cost-effectiveness of physical activity-oriented interventions for improving mental health conditions. Study selection and analysis We searched four databases (PubMed/Medline, Science Direct, PsychArticles, PsychINFO) for published studies (from any time and region) that (1) assessed physical activity-oriented interventions in mental health disorders, (2) undertook a full economic evaluation (and specifically cost-effectiveness analysis or cost-utility analysis), and (3) were in English. Data were extracted from included studies using a predetermined 32-item matrix using the Covidence software platform. Findings Search and screening resulted in 11 studies eligible for inclusion. The incremental cost-effectiveness ratio ranged from £119 to £152,822 per quality-adjusted life year (QALY) gained. Physical activity interventions, including group sessions, such as dance exercise and walking, or one-on-one support through telephone or web-based personalized support and guidance, were found to be cost-effective. However, over half of the interventions (55%) were considered to be not cost-effective. Conclusions Our review found that the current evidence is insufficient to conclude whether physical activity-oriented interventions for mental health are a cost-effective when compared with the standard of care of other treatment types. Better designed studies focusing on specific mental health conditions and physical activity interventions that address cost-effectiveness analysis are warranted. Physical activity-oriented interventions for improving mental health should adopt low-cost implementation strategies and include behavioral economics components.